PENINGKATAN KUALITAS SERAT DAUN PELEPAH KELAPA MELALUI PERLAKUAN ALKALI - Darmanto, Seno; Umardani, Yusuf (ROTASI, 2009)
Research is done to analyze treatment (physical and chemical) in increasing quality of coconut leaves fiber. Plot of coconut leaves fiber research is done with determining characteristic of physically coconut leaves, method of making single fiber, treatment technical and testing of strength. Determining of physically coconut leaves characteristic is done by observing and measuring dimension directly and testing water content. Then making of single fiber is done by selecting of coconut leaves, washing, drying and brushing/shaving. Treatment of physically coconut leaves is begun from coconut leaves in sheet shape to single fiber shape. Kind of physically treatment consists of washing, soaking, natural drying and supervised drying. Washing and soaking use water. Natural drying of coconut leaves is done when coconut leaves is sheet. Supervised drying is done with hot air in ±45oC of temperature. Generation of hot air is done with heat transfer from hot water ±60oC of temperature to air in drying pan. The next, washing, soaking and supervised drying is done to prepare coconut leaves that will be used to chemical treatment. Chemical treatment is done with methode alkali. Alkali treatment to single coconut leaves fiber is done with using NaOH solution. The alkali solution is arranged with concentration variation 5%, 10% and 15%. Alkali treatment uses water as solvent. Testing of single coconut leaves fiber is done to refer JIS number R7601 for single fiber. Observing and measuring shows that coconut leave stem has ±230 of coconut leaves. Measuring dimension shows that coconut leaves width have ±1 cm in coconut leaves tip, ±4 cm in coconut leaves center and ±2 cm in coconut leaves stem tip. Water content of coconut leaves can reach ± 50%. Method of making single fiber show that brushing or shaving will be effective when coconut leave is rather dry. Then testing of tensile shows that alkali treatment is trend to increase strength and elongation. The increasing of coconut leaves quality (strength and elongation) will be optimum in concentration 10% of NaOH.